An Inquiry into Teaching the Perceptual Effects of the Measures to the Students of Architecture - Zanjani, Ali Rahmanpour (Journal of History Culture and Art Research, 2017)
This paper investigates the “increasing level of consideration among students about the effects of environment’s perceptible dimensions on human’s mind”. Firstly, to recognize the topic, with a review in architecture and psychology, it seems that perceptible dimensions in environment have great effects on human’s mind. It is noticeable that mentioned effects are studied in combining format with other constructive elements such as shape and etc. To facilitate access, in first part of a classified information covering different effects of dimensions on human’s feeling and perception are provided to use it to form the educating criteria and to enter in educating architecture. Moreover to determine suitable method of education of basic students related to subject of issue, with investigating related theories about educating methods and referring to expert’s ideas about basic education of architecture and consequently considering their ideas it seems that: with providing opportunities in the form of “students’ guided attendance in environment by moving from instances to concepts” it is possible to simplify learning procedure among basic architecture students using various formats of Learned-Centered Instruction training method. The methodology of this research is based on Deductive-Qualitative approach. Analyzing professors’ interviews is performed to recognize the principles, by accurate coding and combing results, and finally codification an educating format for answering this research’s concern.